Budget preparers' perceptions and performance-based budgeting implementation: The case of Iranian public universities and research institutes. Issue 1 (4th March 2019) - Jalali Aliabadi, Farzaneh; Mashayekhi, Bita; Gal, Graham
Abstract : Purpose: The purpose of this paper is to examine the reason for the failure of implementing performance-based budgeting (PBB) at Iranian public universities and research institutes (PURI). This examination focuses on the actors participating in the budget processes and their perceptions. Design/methodology/approach: The study uses grounded theory and employs deep semi-structured interviews of budget preparers at Iranian PURI. Findings: The results indicate a loose coupling between perceived and regulated budgeting process. This leads to budgetary slack as a barrier for authentic information flow and indeed PBB implementation. In the analysis of the results, the authors suggest some ways to improve the current situation of the budgeting processes at Iranian PURI. Practical implications: Public organizations that desire to transform their budgeting system need to consider their actors' perceptions regarding the budgeting process. By explicitly considering their perceptions the organization may be able to solve any loose coupling as a result of internal, external and behavioral conditions. Originality/value: This research examines issues that arise in the transformation of organizational processes. The focus on budget processes is critical for organizations which receive most, if not all, of their operational funds from a central authority. This research highlights the role of budget actors' perceptions in transforming the budgeting process. An important result of this analysis is documenting the existence of loose coupling in the current budgeting process at Iranian PURI. This loose coupling results in slack creation and restricts the implementation of a PBB system. Additionally, this loose coupling limits the flow of authentic information.